Kajian Buah-Buahan Lokal Unggulan Provinsi Bali dan Potensi Dinamisnya - I Made Tamba (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Bali Province is an area rich in types and varieties of fruit, which must be preserved and promoted sustainably for the community's prosperity. This research aims to (1) analyze superior local fruit in Bali Province and (2) estimate local Balinese fruit that has the potential to become superior fruit or which will be degraded to become non-primed fruit in the future. The fruit production data used as the basis for information in this research is the average production for 2017 to 2023 obtained from Bali Province in Figures 2017–2023 BPS - Statistics Indonesia. LQ analysis is used to analyze superior local Balinese fruit. In contrast, a combination of LQ analysis and LQ growth rate analysis is used to estimate the potential superior fruit of local Balinese fruit in the future. This research showed five types of superior fruit in Bali Province: Siamese oranges, mangosteens, bananas, salacca, and sapodilla. It has been identified that only two types of local fruit will remain Bali's superior fruit in the future, namely mangosteen and salacca. At the same time, Siamese oranges, bananas, and sapodilla are local Balinese fruits indicated to be relegated to non-prime fruit. Water guava, big orange, and soursop are local Balinese fruits promise to become Bali's leading fruit in the future. Based on the results of this research, it is recommended that local Balinese fruits be preserved and even developed sustainably through various multi-party intervention and collaboration programs to provide stimulation so that local Balinese fruits remain strong and growing.